PIP 2 corrects an endothelial Piezo1 channelopathy - Ahmed M. Hashad; Mohammad M. Abd-Alhaseeb; Xin Rui Lim; Natalia M. Mathieu; Osama F. Harraz (Proceedings of the National Academy of Sciences, 2025)
Brain capillaries are sensors of neural activity. When a brain region is active, capillary endothelial cells (ECs) sense neuron-derived mediators and elicit a local increase in blood flow (functional hyperemia) to support the rise in metabolic needs. This hyperemic response involves a rapid electrical component and a slower chemical component that involves Gαq PCR (G q PCR) activation by agonists released from neurons. The intravascular forces associated with hyperemia engage mechanosensitive Piezo1-mediated signaling that serves a mechano-feedback control function to facilitate the return of elevated blood flow to basal levels. Whether G q PCR activity influences Piezo1 mechanosensitive signaling has not been explored, despite the potential significant implications of such crosstalk. Using patch-clamp electrophysiology and freshly isolated brain capillary ECs, we demonstrate that prostanoid or muscarinic G q PCR activation facilitates Piezo1 activity. Pharmacological studies revealed the involvement of Gαq and phospholipase C stimulation, as well as downstream phosphatidylinositol-4,5-bisphosphate (PIP 2 ) hydrolysis in Piezo1 activation, but not signaling triggered by metabolites of PIP 2 hydrolysis. Exogenous application of nanomolar-to-micromolar PIP 2 suppressed Piezo1 open probability. Brain capillary ECs from mouse models of Alzheimer’s disease, cerebral small vessel disease, or Piezo1 gain-of-function mutation exhibited higher Piezo1 activity, that was corrected by exogenous ex vivo PIP 2 application. We finally tested in vivo the hypothesis that systemic PIP 2 administration restores functional hyperemia in EC-specific Piezo1 gain-of-function mutant mice suffering impaired blood flow. Our findings provide insights into Piezo1 channel regulation and how it affects neurovascular coupling and cerebral blood flow.